2011
DOI: 10.1038/jhh.2011.86
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypertension with small, dense low-density lipoprotein in patients without metabolic syndrome

Abstract: A higher proportion of small, dense low-density lipoprotein (sdLDL) is known to be associated with a high prevalence of cardiovascular disease in association with metabolic syndrome (MS). Hypertension (HTN) is one of the known risk factors for MS. However, whether HTN is associated with sdLDL in patients without MS is not yet clear. The lipid profiles, including low-density-lipoprotein (LDL) subfractions, of 383 consecutive subjects were evaluated. The patients without MS consisted of 198 hypertensive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…We found that LDL-MI was higher in patients with NASH than with NAFL despite the two groups having similar LDL-C concentrations. sdLDL has also been reported closely associated with the prevalence of DM [21] , hypertension [22] , dyslipidemia [39] , obesity [40] and chronic kidney disease [24] . Multivariate regression analysis in patients not taking lipid lowering medications showed that increased LDL-MI was independently associated with NASH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We found that LDL-MI was higher in patients with NASH than with NAFL despite the two groups having similar LDL-C concentrations. sdLDL has also been reported closely associated with the prevalence of DM [21] , hypertension [22] , dyslipidemia [39] , obesity [40] and chronic kidney disease [24] . Multivariate regression analysis in patients not taking lipid lowering medications showed that increased LDL-MI was independently associated with NASH.…”
Section: Discussionmentioning
confidence: 97%
“…The surplus triglycerides (TGs) in these livers are therefore transported as TG-rich lipoproteins (VLDL1), a precursor of sdLDL particles [16] , which are a stronger risk factor than low-density lipoprotein cholesterol (LDL-C) for atherosclerotic diseases including CVD [17] [18] . In addition, sdLDL has been associated with several metabolic disorders, including NAFLD [19] [20] , DM [21] , hypertension [22] , obstructive sleep apnea syndrome [23] , and chronic kidney disease [24] . To date, however, no studies have investigated whether sdLDL differs in patients with NAFL and NASH.…”
Section: Introductionmentioning
confidence: 99%
“…However, these associations were not observed in the healthy population. A study comparing LDL subfraction patterns of normotensive and hypertensive individuals without MetS also concluded that hypertension per se did not increase the proportion of sdLDL particles in this population [ 36 ]. Taken together, hypertension is the only factor among components of MetS that is more closely associated to sdLDL-C concentration in MetS than in healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…LDL subfraction is positively correlated with higher waist circumference, higher serum TG, as well as older age and more statin usage in hypertensive patients. Thus, LDL size could represent a risk factor associated with endothelial dysfunction in hypertension [61]. Further, in vitro studies, using cultured endothelial cells, have shown that LDL subfractions from hypercholesterolemic patients may deregulate endothelial function [62].…”
Section: Overweight Obesity and Sdldlmentioning
confidence: 99%